2017
DOI: 10.3341/kjo.2016.0101
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Choroidal Thickness Change of Polypoidal Choroidal Vasculopathy after Anti-vascular Endothelial Growth Factor

Abstract: PurposeTo investigate the peripapillary choroidal thickness (PCT) of polypoidal choroidal vasculopathy (PCV) and exudative age-related macular degeneration (AMD) and to evaluate their responses to anti-vascular endothelial growth factor (VEGF).MethodsThirty eyes with PCV and 25 eyes with exudative AMD who were treatment naïve were included in this study. PCT and subfoveal choroidal thickness were evaluated both before and after intravitreal anti-VEGF.ResultsThe initial mean PCT of PCV (153.78 ± 56.23 µm) was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…We attempt to use this Mask R-CNN model to depict the luminal area and stromal area of choroid layer in order to analyze both choroidal thickness and choroidal vascularity index from OCT images in future study. Recent studies reveal the correlation between the change of choroidal thickness and anti-VEGF injections [38,39]. To explore this association via the proposed model is also part of our future plans.…”
Section: Discussionmentioning
confidence: 90%
“…We attempt to use this Mask R-CNN model to depict the luminal area and stromal area of choroid layer in order to analyze both choroidal thickness and choroidal vascularity index from OCT images in future study. Recent studies reveal the correlation between the change of choroidal thickness and anti-VEGF injections [38,39]. To explore this association via the proposed model is also part of our future plans.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to the macular area, studies on the measurement of CT at the extramacular area have been performed, since the characteristics of the whole body of the patient may also be reflected in the choroid outside of the macula 22 , 24 26 . In addition, measurement of CT at the macular area, and outside of the macula, allows observation of the relative changes in the choroid of the macular area in macular disease 4 , 27 29 . Although many studies have shown changes in macular CT in eyes with AMD or PSDs, few studies have focused on changes in CT outside the macular area 4 , 23 , 27 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, measurement of CT at the macular area, and outside of the macula, allows observation of the relative changes in the choroid of the macular area in macular disease 4 , 27 29 . Although many studies have shown changes in macular CT in eyes with AMD or PSDs, few studies have focused on changes in CT outside the macular area 4 , 23 , 27 , 29 . In this study, we hypothesized that CT profiles, including subfoveal CT, nasal peripapillary CT, and the ratio of subfoveal CT to peripapillary CT, can be the surrogate variables of the choroids in eyes with AMD and PSDs.…”
Section: Introductionmentioning
confidence: 99%
“…No statistical significance was associated with change in choroidal thickness in patients treated with and without PDT (either standard or reduced fluence) or number of injections which was comparable to the study by Giridhar et al 8 Lee et al showed a significant decrease in mean choroidal thickness in PCV patients post anti VEGF therapy. 9 Mean choroidal thickness also decreased at 3 years follow up and was associated with number of intravitreal Ranibizumab injections in yet another study while no significant association between baseline CCT and mean CCT reduction at month 36 was noted by Azuma et al 10 It has been speculated that an increased extra vascular volume and increased choroidal hyper permeability may be associated with a thicker subfoveal choroid which may show a poor response owing to increased hydrostatic pressure. And these studies show a better response to anti VEGF therapy associated with thinner choroid.…”
Section: Discussionmentioning
confidence: 91%